Cu-II-herbicide complexes: structure and bioactivity - Psomas, G; Dendrinou-Samara, C; Philippakopoulos, P; Tangoulis, V; Raptopoulou, C; Samaras, E; Kessissoglou, D (1998)
Copper complexes with the commercial auxin herbicides 2,4-dichlorophenoxy-acetic acid (2,4-D), 3,4-dichlorophenoxy-acetic acid (3,4-D), 2,4,5-trichlorophenoxy-acetic acid (2,4,5-T), 2-methyl-4-chloro-phenoxy-acetic acid (MCPA), 2,3-dichlorophenoxy-acetic acid (2,3-D) and 2-(2,4-dichlorophenoxy)-propanoic acid (2,4-DP) in the presence or not of 2,2′-bipyridine (bipy), an antimicrobial agent, were prepared and characterized. The available evidence supports a dimeric structure for the 2,3-D complex, while the presence of bipy leads to monomeric forms. The solution behaviour of dinuclear complexes in dimethylformamide (DMF) has shown that the complexes are converted to monomeric compounds by the addition of more than 1:2 of bipy. The cyclic voltammograms of dimers in DMF suggest that the complexes retain the dimeric structure in solution. The electron spin resonance spectra of the compound (aqua) (2.2′-bipyridine)bis(2-methyl-4-chloro-phenoxyacetato) copper(II) (1) show features characteristic of the presence of an S = 1 triplet state. The crystal structure of 1 was determined and refined by least-squares methods using three-dimensional Mo Kα data. 1 crystallizes in the space group C2/c, in a cell of dimensions a = 40.49(1), b = 7.286(3). c = 19.617(6) Å, β = 103.23(1)°, V = 5634(3) Å3, Z = 8. Study of the antimicrobial activity showed that the presence of bipy increases the efficiency 4-8 times. © 1998 Elsevier Science S.A. All rights reserved.